A rare case of recurrent polychondritis with aortic valve involvement - N.V. Bortniak; O.A. Yepanchintseva; G.I. Kovtun; S.I. Dorofeieva; O.S. Chumak; G.M. Prus; O.J. Zharinov; B.M. Todurov (Кардіохірургія та інтервенційна кардіологія)
The article presents a clinical case of aortic valve disease and recurrent polychondritis (autoimmune disease) with lesions of cartilage tissue in 68-year-old patient admitted to a cardiac surgery clinic due to need for surgical treatment of aortic heart disease. The results of laboratory and instrumental studies, as well as the morphological study of remote aortic valve are provided. Signs of a recurrent polychondritis appeared in a patient 10 years ago, but the diagnosis was erroneous at the onset of the disease. The most serious and prognostically unfavorable complication was damage to the cardiovascular system – a combined aortic heart disease with a predominance of stenosis with rapidly increasing circulatory decompensation. Because recurrent polychondritis is a rare pathology, due to low awareness and low alertness of physicians, correct diagnosis is established only in 68 % of recurrent polychondritis patients after one year. In diagnosis of this disease, it is necessary to take into account that one of the manifestations of recurrent polychondritis is a typical lesion of cartilaginous part of the ears (edema of the cartilaginous part of auricles).